Dermoscopic and Histopathological Features of Melanocytic Lesions in Melanoma Patients Undergoing Adjuvant Systemic Therapy - Yalcın, Huseyin Berk; Balan, Kerem; Gokoz, Ozay; Elcin, Gonca; Dizdar, Omer; Kılıckap, Saadettin; Gulseren, Duygu (Dermatology Practical & Conceptual, 2026)
Introduction: Melanoma accounts for around 1% of all skin tumors yet is responsible for 80% of deaths related to skin cancer. Although adjuvant therapies improve survival, their effects on nevi remain unclear. Objectives: This study aimed to investigate the dermoscopic and histopathological features of melanocytic nevi in melanoma patients receiving adjuvant systemic therapy. Methods: Dermoscopic images of 1,299 melanocytic nevi from 25 melanoma patients undergoing adjuvant therapy (targeted therapy, immunotherapy, or IFN-α) were analyzed before and after treatment. The histopathological features of 129 excised nevi from 67 melanoma patients were compared between patients who received adjuvant therapy and those who did not. Results: Melanoma patients on targeted therapy showed a greater reduction in global pigmentation and disappearance of the pigment network than those on IFN-α and immunotherapy (p=0.001 and P=0.017, respectively). IFN-α therapy was associated with more atypical pigment network changes than targeted therapy and immunotherapy (P=0.027). Histopathologically, structural atypia, cytological atypia, inflammation, and fibroplasia were more prevalent in excised nevi from patients receiving adjuvant therapy (P=0.003, P=0.004, P<0.001, P=0.020, respectively). Conclusions: Adjuvant systemic therapy induces dermoscopic and histopathological changes in melanocytic nevi. Clinicians and pathologists should carefully consider these alterations during melanoma follow-up to inform treatment decisions.